Faktor-Faktor Yang Mempengaruhi Profitabilitas Perusahaan Otomotif Di Bursa Efek Indonesia - Mirah Sanjiwani, I Gusti Ayu Agung; Suardana, Ketut Alit (E-Jurnal Akuntansi, 2019)
This study aims to empirically examine the effect of cash turnover, accounts receivable turnover, inventory turnover and capital turnover on profitability in automotive companies listed on the Indonesia Stock Exchange for the period 2012-2016. The data used secondary data obtained from the website www.idx.co.id. The analysis technique used is multiple linear analysis. The results show that cash turnover have significant effect on profitability. This shows that the increase in cash turnover of automotive companies tends to increase profitability. Account receivable turnover has significant effect on profitability. This shows that the increase in automotive company accounts receivable turnover tends to increase profitability. Inventory turnover has significant effect on profitability. This shows that the increasing inventory turnover of automotive companies tends to increase profitability. Working capital turnover has significant effect on profitability. This shows that the increase in turnover of working capital of automotive companies tends to increase profitability. Keywords:  Cash turnover, accounts receivable turnover, inventory turnover, working capital turnover, operating profit